2007
DOI: 10.1089/acm.2006.6280
|View full text |Cite
|
Sign up to set email alerts
|

Complementary And Alternative Medicine (CAM) in Palestine: Use And Safety Implications

Abstract: CAM utilization in Palestine is very common. Some of the types of CAM used in Palestine are common elsewhere, whereas other types were unique to this area. The herbal products used by the respondents were mainly collected from nature. Safety of such products is questionable, and contamination cannot be ruled out. Awareness of potential adverse effects and proven benefits of various types of CAM needs to be raised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
5
22
0
2
Order By: Relevance
“…This result is in line with the (61.7%) female participants in a study by Emmett and also 66% reported by Sawalha [9,10]. This shows that nursing is largely dominated by females.…”
Section: Discussion:-supporting
confidence: 91%
“…This result is in line with the (61.7%) female participants in a study by Emmett and also 66% reported by Sawalha [9,10]. This shows that nursing is largely dominated by females.…”
Section: Discussion:-supporting
confidence: 91%
“…Mann-Whitney- U test or Kruskal-Wallis test were used to compare differences as appropriate. P -values of <0.05 were considered statistically significant [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, when a pharmacist fail to efficiently educate CAM users on the best ways to use these products, patients might suffer [20, 21]. There is clear evidence supporting the growing interest in CAM among patients in Palestine [22]. To date, the majority of studies conducted in Palestine have focused on knowledge and attitude of diabetic, hypertensive, cancer, hemodialysis patients, and students pertaining to CAM or herbal use [2328].…”
Section: Introductionmentioning
confidence: 99%
“…Les études publiées montrent une prédominance de l'homéopathie suivie de l'acupuncture [1-10]. L'étude palestinienne retrouve aussi une prédominance des herbes et du miel [9].…”
Section: Discussionunclassified